Educational Data Mining for Mapping Student Ability Based on School Location Using Apriori Method Case Study : SMK YPM Sidoarjo - M. Mahaputra Hidayat; Rifki Fahrial Zainal; Andi Alfian Efendi (Fakultas Teknik Universitas Bhayangkara, 2023)
With the advancement of information technology today, the need for accurate information is needed in everyday life, so that information will become an important element in the development of society today and in the future. However, the high need for information is sometimes not matched by the presentation of adequate information, often the information still has to be re-excavated from very large amounts of data. Traditional methods of analyzing existing data, cannot handle large amounts of data. Basically Senior High School is programmed for those who continue to a higher level, while the provision of skills can be said to be non-existent. Vocational High Schools can produce quality graduates in terms of work skills, therefore currently many companies require graduates from Vocational Schools. The purpose of this study is to create an application to obtain useful information about mapping the value of subjects, especially English at YPM Vocational School in Sidoarjo with data mining techniques and Apriori method. From the results of system testing, it shows that there is still a lack of National Examination Scores for English in most YPM Vocational Schools in Sidoarjo.